Studi perbandingan rencana strategis bank yang terdaftar pada Bursa Efek Indonesia (BEI) - Sabila, Maulia Rosma; Mayasari, Nur Aulia Keysha; Nasikhah, Mazroatun; Fitri, Anis Zakiyah (Maliki Interdisciplinary Journal, 2023)
This study aims to analyze the factors that influence the success of strategies amid increasingly fierce competition in the era of digitalization. In the ever-evolving banking industry, the need to adapt to technology will encourage banks to integrate online banking services to increase their competitiveness. This research involves analyzing corporate strategy, bank viability and the impact of changes in financial technology (Fintech) on banking. The data collection technique used is by taking the strategic plan and literature study.